Getting your science into use: how to have impact - Wollenberg, Eva Karoline (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2019)
Presentation by Lini Wollenberg, CCAFS, at the CLIFF-GRADS workshop on 6-7 October 2019 in Bali.